Agroforestry and biodiversity conservation in tropical landscapes - Schroth, G. (Goetz) (Island Press, 2004)
Annotation Forty-six scientists and practitioners from thirteen countries with decades of field experience in tropical regions explore how agroforestry practices can help promote biodiversity conservation in human-dominated landscapes, synthesise the current state of knowledge in the field, and identify areas where further research is needed.